2010
DOI: 10.1186/1471-230x-10-112
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of genes coding for ghrelin and its receptor in relation to colorectal cancer risk: a two-step gene-wide case-control study

Abstract: BackgroundGhrelin, an endogenous ligand for the growth hormone secretagogue receptor (GHSR), has two major functions: the stimulation of the growth hormone production and the stimulation of food intake. Accumulating evidence also indicates a role of ghrelin in cancer development.MethodsWe conducted a case-control study to examine the association of common genetic variants in the genes coding for ghrelin (GHRL) and its receptor (GHSR) with colorectal cancer risk. Pairwise tagging was used to select the 11 polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Genetic polymorphisms in the GHRL gene may affect GHRL production or protein expression, thereby modulating disease risk. Several studies have reported that GHRL polymorphisms might be associated with obesity [ 25 ], metabolic syndrome [ 27 ], type 2 diabetes [ 29 ], breast cancer [ 30 ], and colorectal cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic polymorphisms in the GHRL gene may affect GHRL production or protein expression, thereby modulating disease risk. Several studies have reported that GHRL polymorphisms might be associated with obesity [ 25 ], metabolic syndrome [ 27 ], type 2 diabetes [ 29 ], breast cancer [ 30 ], and colorectal cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the association between the GHRL rs26311, rs27647, rs696217, and rs34911341 polymorphisms with the risk of various diseases such as obesity [ 25 ], metabolic syndrome [ 27 , 28 ], type 2 diabetes [ 29 ], breast cancer [ 30 ], and colorectal cancer [ 31 ]. Until now, there were only two studies that examined the association between GHRL polymorphisms and the risk of liver diseases [ 17 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 17 Chironomid samples (6, 7, and 4 samples obtained from areas I, II, and III, respectively) were genotyped using the Illumina BovineHD Genotyping BeadChip system (Neogen, Lincoln NE, USA), which contained 419 431 SNPs. DNA was isolated from the organisms using a standard proteinase K digestion followed by phenol/chloroform extraction and ethanol precipitation (Campa et al 2010), and then the DNA concentrations were measured using a Nano-Drop2000 spectrophotometer (ThermoFisher Scientific, Waltham, MA, USA). The integrity of the genomic DNA was confirmed by means of 1% agarose gel electrophoresis.…”
Section: Fieldwork and Samplingmentioning
confidence: 99%
“…In human, GHSR gene polymorphism was reported to have an association with eating behavior (Gueorguiev et al 2009), obesity and glucose metabolism (Mager et al 2008), and colorectal cancer risk (Campa et al 2010). Studies of GHSR gene have been reported in other animals, such as cattle (Komatsu et al 2015), duck (Nie et al 2009), quail (Kitazawa et al 2009), and goldfish (Sánchez-Bretaño et al, 2015).…”
Section: Introductionmentioning
confidence: 99%